Semantics, tense, and time : an essay in the metaphysics of natural language - Ludlow, Peter, 1957- (MIT Press, 1999)
Annotation According to Peter Ludlow, there is a very close relation between the structure of natural language and that of reality, and one can gain insights into long-standing metaphysical questions by studying the semantics of natural language. In this book Ludlow uses the metaphysics of time as a case study and focuses on the dispute between A-theorists and B-theorists about the nature of time. According to B-theorists, there is no genuine change, but a permanent sequence of events ordered by an earlier-than/later-than relation. According to the version of the A-theory adopted by Ludlow (a position sometimes called presentism), there are not past or future events or times; what makes something past or future is how the world stands right now.
"A Bradford book."
Keywords: Semantics.; Language and languages -- Philosophy.; Time.; Metaphysics.; Grammar, Comparative and general -- Tense.; First philosophy.; Semantics; Time; Metaphysics; Sémantique.; Langage et langues -- Philosophie.; Temps.; Métaphysique.; Temps (Linguistique); semantics.; time.; metaphysics.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Semantics.; First philosophy; Grammar, Comparative and general -- Tense; Language and languages -- Philosophy; Tijd.; Semantiek.; Metafysica.